The effect of total hysterectomy on sexual function and depression - Göktaş, Sonay Baltacı; Gün, İsmet; Yıldız, Tülin; Sakar, Mehmet Nafi; Çağlayan, Sabiha (Professional Medical Publications, 2015)
Background & Objectives: To investigate whether the operations of Type 1 hysterectomy and bilateral salpingo-oophorectomy performed for benign reasons have any effect on sexual life and levels of depression. Method: This is a multi-center, comparative, prospective study. Healthy, sexual active patients aged between 40 and 60 were included into the study. Data was collected with the technique of face-to-face meeting held three months before and after the operation by using the demographic data form developed by the researchers i.e. the Female Sexual Function Index (FSFI) and the Beck Depression Scale (BDS). Results: In the post-operative third month, there was an improvement in dysuria in terms of symptomatology (34% and 17%, P<0.001), while in FSFI (41.47 +/- 25.46 to 34.20 +/- 26.67, P<0.001) and BDS (12.87 +/- 11.19 to 14.27 +/- 10.95, P=0.015) there was a deterioration. For FSFI, 50-60 age range, extended family structure; and for BDS, educational status, not working and extended family structure were statistically important confounding factors for increased risk in the post-operative period. Conclusion: While hysterectomy and bilateral salpingo-oophorectomy performed for benign reasons brought about short-term improvement in urinary problems after the operation for sexually active and healthy women, they resulted in sexual dysfunction and increase in depression. The age, educational status, working condition and family structure is also important.
WOS: 000358188800041
PubMed ID: 26150871
Keywords: Depression; Female; Hysterectomy; Sexual Dysfunction; Sexuality